Role of E-cadherin in epithelial architecture maintenance - Izaguirre, María Fernanda (2010)
Morphogenesis and architecture of a developing epithelium is controlled by both cell shape and contacts, mediated by spatially and temporally regulated cell adhesion molecules. The authors study if E-cadherin functions as a key factor of epithelial adhesion and epidermal architecture in vivo. They apply whole-mount digital deconvolution microscopy to evaluate three-dimensional (3D) E-cadherin expression during skin morphogenesis of Rhinella arenarum and in a cell adhesion alteration model. Results show morphogenetic changes in the 3D E-cadherin spatiotemporal expression pattern correlated with the increase of E-cadherin and in the number of cells with hexagonal geometry. Alterations in junctionprotein phosphorylation showed drastic loss of E-cadherin and β-catenin in cell-cell contacts and the increase of cytoplasm and nuclear β-catenin in epidermis, suggesting the activation of the β-catenin signal pathway. Surprisingly, no changes in cell shape and skin architecture were registered, suggesting that epidermal E-cadherin appears to be involved in signaling rather than cell contact maintenance in vivo.